1996
DOI: 10.1093/infdis/174.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Interleukin (IL)-8 Gene Expression by Respiratory Syncytial Virus Involves Activation of Nuclear Factor (NF)- B and NF-IL-6

Abstract: Respiratory syncytial virus (RSV) preferentially infects respiratory epithelium and is an important cause of lower respiratory tract infections in young children. RSV induces the production of interleukin (IL)-8 in airway epithelial cells; however, the mechanism of this induction is not known. To define the mechanism by which RSV induces IL-8 gene activation, A549 epithelial cells were transfected with plasmids containing serial deletions of the 5'-flanking region of the IL-8 gene and then exposed to RSV for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 19 publications
9
111
1
Order By: Relevance
“…Rosiglitazone, when applied at high concentrations (50 mM), had a significant but an inferior inhibitory effect on TNF-a-induced IL-6 production compared with genistein, which also inhibited both endogenous and TNF-a-induced C/EBP-b, a transcription factor involved in inflammation 23 and adipocyte differentiation, 24 as well as p65 unit of NF-kB. Promoters of IL-6 and IL-8 have binding sites for both C/ EBP-b and NF-kB, 18,19 and functional and physical associations between NF-kB and C/EBP have been shown. 25 The inhibitory effect of genistein on NF-kB-mediated transcription of IL-6 has been shown 20 and we have presented, in this study, that genistein inhibits the binding of C/EBP-b on the IL-8 promoter.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rosiglitazone, when applied at high concentrations (50 mM), had a significant but an inferior inhibitory effect on TNF-a-induced IL-6 production compared with genistein, which also inhibited both endogenous and TNF-a-induced C/EBP-b, a transcription factor involved in inflammation 23 and adipocyte differentiation, 24 as well as p65 unit of NF-kB. Promoters of IL-6 and IL-8 have binding sites for both C/ EBP-b and NF-kB, 18,19 and functional and physical associations between NF-kB and C/EBP have been shown. 25 The inhibitory effect of genistein on NF-kB-mediated transcription of IL-6 has been shown 20 and we have presented, in this study, that genistein inhibits the binding of C/EBP-b on the IL-8 promoter.…”
Section: Discussionmentioning
confidence: 97%
“…Genistein Inhibits Endogenous and TNF-a-Induced p38, C/EBP and NF-jB Pathways As both genistein and p38 inhibitor, SB203580, inhibited endogenous and TNF-a-induced synovial fibroblasts IL-6 and IL-8 production (Figure 2c and d), and because promoters of IL-6 and IL-8 have binding sites for both C/EBP-b and NF-kB, 18,19 we have tested the effect of TNF-a and PPAR-g agonists on the expression of these proteins in synovial fibroblasts. Western blots showed that TNF-a induced phosphorylation of p38, and expression of p38, C/EBP-b and p65 unit of NF-kB ( Figure 3).…”
Section: Statisticsmentioning
confidence: 99%
“…28 Detailed studies of IL-8 expression have shown that AP-1, IFN regulatory factor (IRF)-1 and C/EBP b are all necessary for RSV-induced induction of the IL-8 promoter. 13,29 Moreover, NF-kB and C/EBP b binding at the promoter synergistically activate IL-8 in response to Figure 4 Screening for differences in allele-specific binding of nuclear proteins at IL-8 polymorphisms using EMSAs with nuclear extracts from A549 cells after incubation with TNF (a) or RSV (b). (a) When incubated with nuclear extracts from A549 cells, no significant allele specific differences in binding could be seen at the À251 (lanes 1 and 2), the þ 1238 polymorphism (lanes 7 and 8) and the þ 1633 polymorphism (lanes 9 and 10).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional regulation of IL-8 expression has been described as involving NF-B, AP-1, and NF for IL-6 (NF-IL-6) promoter sequences (19,20). TNF-␣-induced transcription from the IL-8 promoter activates the classical NF-B pathway in the A549 airway cell line (4).…”
Section: L16mentioning
confidence: 99%